Training on Qualitative Methods in Writing Scientific Papers for Students: Learning Data Collection and Data Analysis - Tira Nur Fitria (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
This training activity provides information and knowledge to students about qualitative research methodology in doing their final project, thesis, and the task of writing articles that are being programmed. The method of implementing this activity uses the lecture and discussion (Q&A method). This activity was held on Tuesday, April 26, 2022, via Zoom Meeting and YouTube Live Streaming. Participants consist of 55 students majoring in S1 Sharia Economics from ITB AAS Indonesia. The lecturer as the speaker presents material about qualitative research methods including the definition, characteristics, and data collection methods such as primary data (interview, questionnaire, and observation) and secondary sources (document), then data validation (triangulation) and data analysis methods (data reduction, data display, and conclusion). Â The lecturer as a speaker also provides an opportunity for participants (students) to ask questions in the raise hands, Zoom chat column, or live YouTube chat. These Q&A answers show the participantsâ€™ activeness in participating in the activity and the enthusiasm of the activity participants in asking the lecturer (speaker) regarding the qualitative research method material that has been explained. The follow-up of this activity is holding similar activities that focus more on implementing data analysis in the findings and discussion section.